Corporate governance in the Middle East and North Africa - Pierce, Chris (GMB, 2008)
This authoritative guide looks at corporate governance in the Middle East and North Africa. It asseses the region's regulatory framework and how issues such as corporate structure, ownership, boards disclosure and accountability, shareholder rights, stakeholder relations, directors duties, and environmemtal and social responsibility are perceived and addressed in this booming region.